2021
DOI: 10.3390/healthcare9050568
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Sleep Characteristics in Myalgic Encephalomyelitis/Chronic Fatigue Syndrome

Abstract: (1) Background—Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a multifaceted illness characterized by profound and persistent fatigue unrelieved by rest along with a range of other debilitating symptoms. Experiences of unrefreshing and disturbed sleep are frequently described by ME/CFS patients. This is the first systematic review assessing sleep characteristics in ME/CFS. The aim of this review is to determine whether there are clinical characteristics of sleep in ME/CFS patients compared to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Positive studies: non-restorative sleep, restlessness, insomnia, sleep apnea more common in people with ME/CFS (187), although formal sleep laboratory studies have produced inconsistent results (188,189). Meta-analysis of studies of ˜1300 adults and adolescents finds longer sleep latency, reduced sleep efficiency, increased longer REM latency, longer bedtime, and altered sleep microstructure (190).…”
Section: Sleep Disordersmentioning
confidence: 99%
“…Positive studies: non-restorative sleep, restlessness, insomnia, sleep apnea more common in people with ME/CFS (187), although formal sleep laboratory studies have produced inconsistent results (188,189). Meta-analysis of studies of ˜1300 adults and adolescents finds longer sleep latency, reduced sleep efficiency, increased longer REM latency, longer bedtime, and altered sleep microstructure (190).…”
Section: Sleep Disordersmentioning
confidence: 99%
“…At the same time, IAF is associated with the features of the white matter structure (fiber density, axon diameter, myelination), and also reflects various other neuronal processes [30]. In turn, PAF is associated with reduced cerebral blood flow and reduced brain oxygenation and correlates negatively with subjective assessments of fatigue, including total fatigue [31] and cognitive readiness [32], including worse results in memory tasks [33] (fig. 3).…”
Section: Iv1 Eegmentioning
confidence: 99%
“…Research using various self-report measures found that 87–95% of ME/CFS patients reported unrefreshing sleep [ 1 , 25 28 ], and ME/CFS patients showed significantly poorer sleep quality and more daytime dysfunction compared to healthy controls [ 29 31 ]. In contrast, studies implementing objective sleep measures [ 32 ] often did not observe more sleep-related difficulties in those with ME/CFS than in healthy controls [ 33 35 ].…”
Section: Introductionmentioning
confidence: 99%